Wykorzystanie metod WAP do wyodrębniania profili lokalnej polityki ekonomicznej - Wędrowska, Ewa; Wojarska, Magdalena (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The main aim of that article is an identification of local policy types in the region of Warmia and Masuria. Empirical material was piled during local research with use of categorized individual interview in August 2002 year. 39 expediently selected local authorities participated in the research. One of cluster analysis' method has been used for singling out packages of similar objects. Base of singling out has been following variables: subjective estimate of realized policy; formal and informal operations taken by self-governed authorities; manners of prompting of local enterprises; degree of engagement of subject of local policy to process of privatization of public sector enterprises. Three packages of gminas have been received in effect in the field of economic policy. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 333-340